Identification and characterisation of heat-stable allergens from Sarcoptes scabiei - Tarigan, Simson (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Animals or human recovered from Sarcoptes scabiei infestation acquired protective immunity against reinfestation. The protective immunity is considered to be associated with a type-1-hypersensitivity reaction against allergens instigated by the mites during infestation. It is assumed that these allergens have the potential to be used as the main component of an anti-scabies vaccine. The purpose of this study is to identify and characterise the sarcoptic allergens. For this purpose, 645 mg of mites, collected from mangy goats, were homogenised in PBS to prepare soluble mite proteins. Fractionation of proteins was initially performed on a Q-sepharose column but the results were unsatisfactory. Consequently, SDS PAGE was used as an alternative. Proteins from the gel were transferred onto a nitrocellulose membrane. The membrane was cut into strips so each strip contained proteins with molecular weights of Â³ 90, 80-90, 70-80, 60-70, 50-60, 40-50, 30-40, 25-30, 20-25, 15-20 and 10-15 kDa, respectively. The heat stability of the allergens was determined by heating the suspension at 60ÂºC for 60 minutes, whereas their dialysability was evaluated using a 10-kDa-cut-off ultramembrane. The activity of the allergens was assayed by an intradermal test on sensitised goats. This study showed that mite protein extract was very potent allergens since mite extract containing as little as 1 ng mite proteins still caused an obvious hypersensitive reaction. The mite extract contained heat-stable, dialysable and non-dialysable allergens. All fractions recovered from a Q-sepharose column contained allergens with almost equal potency. Fractionation with the SDS-PAGE revealed that the allergens had molecular weights of 35 and <10 kDa. The former allergen is assumed to be a member of group 10 allergens, whereas the later belong to haptenic allergens. Kata Kunci: Sarcoptes Scabiei, Allergens, Heat-Stable, Group 10, Hapten